The anarchist before the law : law without authority / Saul Newman and Massimo La Torre. - Newman, Saul, 1972-; La Torre, Massimo (Encounters in law and philosophy., 2024)
When might an anarchist need a good lawyer? Why do radical activists committed to revolutionary change often have to work within the limits of the law? Can a judge also be an anarchist? This book is an exploration of a paradoxical, yet necessary, encounter between anarchism and the law. Anarchism offers the most radical critique of the principle of legal authority and, as such, poses essential questions that legal philosophy must respond to regarding political obligation and the legitimacy of coercion. At a time when the law is in a state of crisis, it becomes crucial to interrogate its founding principles and ethical limits.